Application of orthokeratology on myopia control and its effect on ocular surface and meibomian gland function in Chinese myopic adolescents - Hui, Wang; Xiao-feng, Hu; Song-guo, Li; Jing-jing, Wang; Xuan, Huang; Yong, Tao (Frontiers in Medicine, 2022)
Purpose To investigate the influence of orthokeratology (OK) on myopia control and ocular surface and meibomian gland function in myopia adolescents. Methods A prospective study conducted over a 12-months period. Subjects were divided into two groups: the OK lens group and the frame glasses control group. Axial length, corneal curvature, ocular surface and meibomian gland parameters were measured at baseline, 1, 3, 6 and 12 months after wearing OK lenses. Results The axial length growth rate in the OK group was significantly slower than in the control group (P < 0.01). The naked eye vision and ocular surface disease index (OSDI) scores recorded 1, 3, 6 and 12 months after wearing OK lenses were significantly higher than the scores recorded before wearing OK lenses. There was no significant difference in other ocular parameters at each follow-up time points compared with pre-wearing (P > 0.05). After using OK lens for 6 months, the OSDI score and corneal fluorescein staining score increased significantly (P < 0.001), but there were no significant differences in other parameters among the groups. No infectious keratitis occurred during the study. Conclusion These results provide evidence that the use of OK lenses can control the axial growth and myopia progress rate compared with frame glasses. During the 12-month follow-up, although wearing OK lenses may have aggravated dry eye symptoms, each patient’s ocular surface and meibomian gland function did not change significantly, indicating that OK is a relatively safe modality for the correction of myopia in adolescents.